Professional ethics in postgraduate students from two Mexican universities - Cecilia Navia Antezana; Ana Hirsch Adler (Universidad Autónoma de Baja California, 2014)
This article presents the results of research on professional ethics in two Mexican universities: the National Autonomous University of Mexico, with the research project Professional Ethics, and the Autonomous University of the State of Morelos with the project Professional Ethics in Teacher Training. Both research projects shared significant elements: objectives, theoretical framework, use of postgraduate students as study subjects, an instrument for data collection and methodology of analysis. We found a strong presence of cognitive and ethical skills, although one of the ethical skills, "Providing the best service to society", received a low percentage. Significant contradictions with regard to the ethical values "Continuing Education", "Hardworking" and "Respect" were found.